A wild west ride - Osborne, Mary Pope; Masson, Philippe (London Red fox, 2022)
In the series "Magic Tree House" we meet Jack, eight and a half, and his seven-year-old little sister, Annie, who find a cabin in a tree. In the cabin they find books, and when they wish to go to the place where the action in the book takes place, they get there. The cabin is a time machine. They are whirled into other times, and are exposed to the challenges of the different times, pirates, mummies, knights and dinosaurs. They are saved home by returning to the cabin and looking at a book with a picture of the house they live in
English stories
Keywords: English fictions